EXPLORING THE PROHIBITION OF SMOKING IN ISLAM: A LITERATURE REVIEW ON QUR'ANIC VERSES, SUNNAH, AND I'TIBAR PERSPECTIVES WITH EMPHASIS ON HEALTH IMPLICATIONS - Rosyada, Dede; Filhaq, Raghib; Fadlilah, Dina Rahma; Nahuda, Nahuda; Syahrullah, Syahrullah (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Smoking is prohibited based on the meanings indicated in the text of the Qur'an and Sunnah and the correct I'tibar (logic). The evidence from the Qur'an is His words Qs. Al-Baqarah 195. This research uses the literature review method in which researchers conduct a series of studies involving various kinds of information derived from literature such as books, journals, documents, and so on with the aim of finding various kinds of theories and ideas which can then be formulated results in accordance with the objectives of the research carried out in order to obtain conclusions about smoking in the perspective of Islam and health. The results of various sources of literature show that Islam has explained well in the Qur'an and hadith regarding smoking in the view of Islam and health. Because smoking can lead to destruction, which damages the entire body system and causes disease from this reason it is very clear that smoking is prohibited or haram. Therefore, avoid cigarettes and get used to healthy living